Use of Spectacles after Cataract Surgery - Tinner, Chiara; Eppenberger, Leila; Golla, Kathrin; Mohanna, Safa; Schmid, Martin K.; Thiel, Michael (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose The goal of this study was to investigate the use of spectacles in everyday life after bilateral cataract surgery with a preoperative refractive target of emmetropia in both eyes. In addition, we analyzed the total cost of spectacles and the patientʼs visual satisfaction at least 6 months after surgery.Methods Patients after bilateral cataract surgery with implantation of an aspheric monofocal IOL (Tecnis 1, Johnson & Johnson) with a preoperative refractive target of emmetropia in both eyes and a documented refractive outcome were included in this prospective observational study. In a phone interview ≥ 6 months after surgery, the following items were assessed: type of spectacles purchased and overall cost, type of activity with and duration of spectacle wear, and satisfaction with the visual situation.Results Seventy patients were included in this study. Depending on their postoperative refraction, patients were divided into group A (n = 27) with perfect emmetropia in both eyes (i.e., spherical equivalent [SE] of ≥ − 0.25 D to ≤ + 0.25 D), group B (n = 21) with achieved emmetropia in one eye (i.e., SE of ≥ − 0.25 D to ≤ + 0.25 D) and a myopic refraction in the other eye (< − 0.25 D), and group C (n = 22) with bilateral myopic results (SE of < − 0.25 D). Overall, 84% of patients had purchased new spectacles, mostly varifocals (59%) or reading glasses (24%) at the median cost of 980 Swiss Francs (mean: CHF 912 ± 746). Despite patientsʼ initial reasoning for their lens choice to require reading glasses only, varifocal glasses were worn for more than 50% or all of awake time by 48% of patients in group A, 43% in group B, and 68% in group C. Despite their regular spectacles use, patientsʼ visual satisfaction was very high in all three groups.Conclusions Most patients who achieve perfect bilateral emmetropia after implantation of monofocal aspheric lenses buy varifocal spectacles within 6 months, and more than half of all patients use their varifocal spectacles for more than 50% of their awakening time. The costs for such spectacles are high.
Keywords: cataract; spectacle use; patient satisfaction; aspheric monofocal intraocular lens